Urban Film and Everyday Practice Bridging Divisions in Johannesburg - Parker, Alexandra; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
This book explores the ways in which films of Johannesburg assist residents of the city to bridge the divisions and inequalities of contemporary urban space through the four lenses of materiality, identity, mobility, and crime. Films influence the everyday practices of urban residents and contribute to their knowledge of the city. Urban Film and Everyday Practice examines the relationship between the city, and its representations through the four themes, to deconstruct the complexity of the city and to understand the complicated nature of residents' interactions with urban space. Johannesburg serves as a case study for examining the divisions and inequalities that cities around the globe are currently facing. .
1 Film in Divided Cities -- 2 Johannesburg the Divided city -- 3 Physical Materiality and Imageability -- 4 Identity -- 5 Mobility -- 6 Crime and the Tsotsi -- 7 The Influence of Film -- Annexure: Method.
Keywords: Motion pictures-History.; Sociology, Urban